Limitations of Current AHA Guidelines and Proposal of New Guidelines for the Preparticipation Examination of Athletes. Issue 6 (November 2015) - Dunn, Tim P.; Pickham, David; Aggarwal, Sonya; Saini, Divya; Kumar, Nikhil; Wheeler, Matthew T.; Perez, Marco; Ashley, Euan; Froelicher, Victor F.
Abstract : Objective: To examine the prevalence of athletes who screen positive with the preparticipation examination guidelines from the American Heart Association, the AHA 12-elements, in combination with 3 screening electrocardiogram (ECG) criteria. Design: Observational cross-sectional study. Setting: Stanford University Sports Medicine Clinic. Participants: Total of 1596 participants, including 297 (167 male; mean age, 16.2 years) high school athletes, 1016 (541 male; mean age, 18.8 years) collegiate athletes, and 283 (mean age, 26.3 years) male professional athletes. Main Outcome Measures: Athletes were screened using the 8 personal and family history questions from the AHA 12-elements. Electrocardiograms were obtained for all participants and interpreted using Seattle criteria, Stanford criteria, and European Society of Cardiology (ESC) recommendations. Results: Approximately one-quarter of all athletes (23.8%) had at least 1 positive response to the AHA personal and family history elements. High school and college athletes had similar rates of having at least 1 positive response (25.9% vs 27.4%), whereas professional athletes had a significantly lower rate of having at least 1 positive response (8.8%, P < 0.05). Females reported more episodes of unexplained syncope (11.4% vs 7.5%, P = 0.017) and excessive exertional dyspnea with exercise (11.1% vs 6.1%, P = 0.001) than males. High school athletes had more positive responses to the family history elements when compared with college athletes ( P < 0.05). The percentage of athletes who had an abnormal ECG varied between Seattle criteria (6.0%), Stanford criteria (8.8%), and ESC recommendations (26.8%). Conclusions: Many athletes screen positive under current screening recommendations, and ECG results vary widely by interpretation criteria. Clinical Relevance: In a patient population without any adverse cardiovascular events, the currently recommended AHA 12-elements have an unacceptably high rate of false positives. Newer screening guidelines are needed, with fewer false positives and evidence-based updates.